Pengungkapan Corporate Social Responsisbility dan Manajemen Laba Dengan Board Gender Diversity Sebagai Variabel Moderasi - Larasati, Meidy Dwi; Az'mi, Yanis Ulul (E-Jurnal Akuntansi, 2023)
Corporate social responsibility can be used as a company's self-defense if the company performs earnings management because it can protect the company's image reputation. The research aims to examine the effect of Corporate Social Responsibility on earnings management with a gender diversity board as a moderator. The research population includes companies that are members of the LQ-45 index on the Indonesia Stock Exchange for the 2018-2020 period. The sampling technique used was purposive sampling with several predetermined selection criteria and 38 companies were obtained. The analytical method used is moderated regression analysis. The results showed that corporate social responsibility and board gender diversity had no significant effect on earnings management, and the board gender diversity was not able to moderate the CSR variable on earnings management. Contributing research could increase the number of women on the board. Keywords: Corporate Social Responsibility; Board Gender Diversity; Earnings Management.